2020
DOI: 10.1021/jacs.0c10907
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorescent Gold Cluster Assembly

Abstract: The photoluminescence (PL) of metal nanoclusters (NCs), originating from their molecule-like electronic structure, is one of the most intriguing properties of NCs. Although various strategies such as tailoring the size, structure, and chemical environment of NCs have shown to improve the PL, their quantum yields (QYs) are still lagging far behind those of conventional luminescent materials, including quantum dots and organic fluorophores. Herein, we report the synthesis of highly luminescent gold cluster assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 86 publications
3
91
0
Order By: Relevance
“…The Hyeon group recently reported that the Au cluster assembly emits greenish‐blue light with ~90% QY 162 . The synergistic effect of unique aurophilic interactions among Au 4 clusters and the rigidified chemical environment induced by Zn 2+ chelation through carboxylate groups is responsible for the strong greenish‐blue fluorescence (λ em = 485 nm).…”
Section: Applicationsmentioning
confidence: 99%
“…The Hyeon group recently reported that the Au cluster assembly emits greenish‐blue light with ~90% QY 162 . The synergistic effect of unique aurophilic interactions among Au 4 clusters and the rigidified chemical environment induced by Zn 2+ chelation through carboxylate groups is responsible for the strong greenish‐blue fluorescence (λ em = 485 nm).…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, AuNC@MUA may potentially be used in detecting methanol in fake alcohol. The methanol detection mechanism is as follows: the PL intensity of the AuNCs was closely related to the polarity of the surface ligands and solvent environment [ 27 , 28 , 45 ]. The ligand of the AuNC, the MUA was covalently bound to the gold core via sulfhydryl group and exposed carboxyl groups on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also showed that the charge state and the ligands played important roles in the luminescence of AuNCs [ 19 , 24 , 25 ]. In 2012, Zheng divided AuNCs into few-atom nanoclusters and few-nanometer nanoclusters [ 26 ]; the luminescence mechanism of the former was revealed partially [ 27 , 28 ]. Nevertheless, the sources of emission for the latter were still difficult to attribute clearly.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a wide variety of unique AIE systems based on organic chromophores and inorganic metal clusters have been explored intensively, broadening their advanced applications in chemical sensing, bioimaging, and optoelectronics. [6][7][8] More recently, guided by Zn 2+ -controlled AIE mechanism, Hyeon et al [9] reported highly luminescent gold cluster assembly (quantum yield of ≈90% in water) from completely nonluminescent Au 4 clusters. Liu and co-workers applied AIE strategy into the design of organic probe emitting in the second near-infrared window (NIR-II, 1000-1700 nm) and used them for brain-tumor precise imaging.…”
Section: Introductionmentioning
confidence: 99%